2013
DOI: 10.1161/circimaging.113.000448
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary and Noninvasive Imaging for Prediction of Distal Embolization and Periprocedural Myocardial Infarction During Native Coronary Artery Percutaneous Intervention

Abstract: T he incidence of periprocedural myocardial infarction (MI) after percutaneous coronary intervention (PCI) ranges from 2% to 50%, depending on the clinical presentation, type of procedure, choice of biomarker (creatine kinase [CK]-MB or troponin), and the threshold used to qualify the diagnosis. 1 Because of this heterogeneity of definition, the prognostic implications of periprocedural MI are controversial. However, several studies have demonstrated that periprocedural MI is associated with worse in-hospital,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 91 publications
0
8
0
2
Order By: Relevance
“…Patel et al has performed similar review regarding the comparison on coronary imaging for prediction of PMI, and raised several discussions about procedural safety and merit, modification of PCI strategy [47]. Intracoronary imaging is generally a safe procedure, and may allow PCI optimization to reduce the risk of PMI from causes other than distal embolization, such as side branch occlusion or incomplete lesion coverage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patel et al has performed similar review regarding the comparison on coronary imaging for prediction of PMI, and raised several discussions about procedural safety and merit, modification of PCI strategy [47]. Intracoronary imaging is generally a safe procedure, and may allow PCI optimization to reduce the risk of PMI from causes other than distal embolization, such as side branch occlusion or incomplete lesion coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Statins are regarded as an important agent for the prevention of PMI. Takano et al [47] demonstrated that low-dose rosuvastatin was sufficient for patients who are already taking statins. A meta-analysis of Wang et al [48] demonstrated that in 24 RCTs with a total of 5526 patients, high-dose statin pretreatment was associated with 59% relative reduction in PMI (odds ratio [OR]: 0.41; 95% confidence interval [CI]: 0.34–0.49; P  < 0.00001) and 39% relative reduction in MACE (OR: 0.61; 95% CI: 0.45–0.83; P  < 0.002).…”
Section: Medical Treatment On Pmi After Pcimentioning
confidence: 99%
“…Potential clinical strategies to mitigate this risk include vasodilator administration (nicardipine is the authors' preferred medication due to longer half-life and modest hypotensive effect), aggressive anticoagulation (with addition of a glycoprotein IIb/IIIa inhibitor, which is usually given as bolus only without post-PCI infusion), attempts for plaque "vaporization" (e.g., by using laser), and deployment of an embolic protection device (usually a filter that can capture both embolized plaque and/or thrombus) (12). Although these steps are logical, their Third, fibroatheroma detection within a lesion treated with PCI may allow for optimal stent selection (13).…”
Section: Fibroatheroma Detected: Now What?mentioning
confidence: 99%
“…9,10 To gain insight into whether the non-obstructive plaque results from repetitive silent ruptures, displays features of plaque rupture, erosion, thin-cap fibroatheromas, chronic occlusion with spontaneous recanalization, and the extent of vascular remodeling, virtual histology intravascular ultrasound, near-infrared spectroscopy, or optical coherence tomography can be deployed. [11][12][13] If there is no evidence of hemodynamically significant epicardial stenoses by FFR or ominous signs of acute intravascular pathology on intracoronary imaging in the presence of angiographically moderate CAD, we would next recommend measuring coronary flow reserve (CFR) to assess the of combination epicardial and microvascular flow in aggregate. If the CFR is \2, the patient has combined epicardial and microvascular dysfunction, with the FFR value providing information of the relative contribution of epicardial stenosis to the total ischemia.…”
mentioning
confidence: 99%